Structural plasticity of a designer protein sheds light on β‐propeller protein evolution. (25th May 2020) - Mylemans, Bram; Laier, Ina; Kamata, Kenichi; Akashi, Satoko; Noguchi, Hiroki; Tame, Jeremy R. H.; Voet, Arnout R. D.
Abstract : β‐propeller proteins are common in nature, where they are observed to adopt 4‐ to 10‐fold internal rotational pseudo‐symmetry. This size diversity can be explained by the evolutionary process of gene duplication and fusion. In this study, we investigated a distorted β‐propeller protein, an apparent intermediate between two symmetries. From this template, we created a perfectly symmetric 9‐bladed β‐propeller named Cake, using computational design and ancestral sequence reconstruction. The designed repeat sequence was found to be capable of generating both 8‐fold and 9‐fold propellers which are highly stable. Cake variants with 2–10 identical copies of the repeat sequence were characterised by X‐ray crystallography and in solution. They were found to be highly stable, and to self‐assemble into 8‐ or 9‐fold symmetrical propellers. These findings show that the β‐propeller fold allows sufficient structural plasticity to permit a given blade to assemble different forms, a transition from even to odd changes in blade number, and provide a potential explanation for the wide diversity of repeat numbers observed in natural propeller proteins. Database: Structural data are available in Protein Data Bank database under the accession numbers 6TJB, 6TJC, 6TJD, 6TJE, 6TJF, 6TJG, 6TJH and 6TJI . Abstract : Computational protein design was applied on a distorted β‐propeller resulting in a perfectly symmetrical 9‐bladed propeller. The designed sequence was also able to fold as an 8‐bladed propeller. Our finding illustrates that the β‐propeller fold allows structural plasticity explaining the variety of repeats found in nature for these proteins.